EVALUATING THE SUN’S POSITION AND TRACKING THE SUN PATH FOR DUTSIN-MA, KATSINA STATE, NIGERIA - Mustapha, Mustapha Shehu; Baraya, J. T. (FUDMA JOURNAL OF SCIENCES, 2020)
Solar energy is the most promising renewable energy source because of its free availability and an environmentally friendly source. The crucial applications of solar energy depend upon determining the precise position of the sun. In this research, we had made an attempt to determine the precise location of the sun for any topographical position of the earth using solar azimuth/altitude reckoner to track the path of the sun and related sun data. For the purpose of this work, we measured the position of Dutsin-Ma in Katsina State, Northwestern part of Nigeria. Solar online calculator (Keisan online calculator) was used to obtain primary data of sun’s (solar) angle parameters in order to calculate a series of variations in the azimuth and altitude angles using some inputs such as latitude, longitude, date, year, time and time zone. The results revealed that the maximum azimuth angles obtained from the sun are 294.38° for the winter solstice and 248.32° for the summer solstice with elevation angles of 79.01° and 53.46° respectively. Furthermore, the highest values of the hour angles were found to be 97.05° and 97.86° for the summer solstice and the winter solstice respectively. The findings of this work will help individual, government, and non-governmental organizations towards the utilization of solar energy and harnessing it especially during the installations of solar panels and other solar devices.